Supply chain integration through community cloud: Effects on operational performance. Issue 2 (June 2016) - Bruque-Cámara, Sebastián; Moyano-Fuentes, José; Maqueira-Marín, Juan Manuel
Abstract: In this paper we analyze the effects exerted by a specific type of cloud technology (community cloud computing) on a particular type of supply chain integration (integration of informational and physical flows). We also analyze the combined effect of community cloud computing and physical-informational supply chain integration on firms' operational results. To test the hypotheses in this paper we use a sample of 394 companies randomly selected from a population of 2036 companies with a staff of at least 50 employees, taken from the DUNS 50, 000 database for companies in Spain. We use factorial analyses and structural equation modeling to test our hypotheses. Our three hypotheses are confirmed, indicating that the community cloud exerts a positive and significant effect both on the informational-physical integration of the supply chain and on operational performance. The value of this study lies in the fact that it enables academics and practitioners to understand which parts of a relatively new technology (cloud technology and its sub-types) might contribute to integrating flows in the supply chain and, ultimately, impacting operational performance. Highlights: Community Cloud intensive use is associated to higher levels of Supply Chain Integration. Informational and Physical Integration is highly related to a higher use of Community Cloud. Operational Performance is also related to the Supply Chain Integration and to Community Cloud deployment.